Formal Thinking Patterns (Monarchy-Hierarchy-Anarchy-Minority) and their Relationship to Academic Grit among Students at Al-Mustansiriyah University (Journal Of Educational and Psychological Researches, 2024)
Thinking certainly has negatives as well as positives in the lives of students, especially its role in raising the academic level of students. It may have a negative effect on academic determination if a certain style is used. Therefore, the current research aims to find out the most significant pattern in the sample and whether it correlates with academic determination. This required the use of Sternberg's scale (1991) in addition to Duckworth and Quinn's determination scale (2009), which was translated by Mahmoud in 2023. The results indicated the significance of the monarchy, hierarchical, minority, and anarchic styles, respectively. When comparing the patterns according to gender, it was found that the patterns are not significant except for the minority and in favor of females, and there is no difference between married and unmarried people in the patterns. In addition to the significance of determination for the sample and in favor of males, there is no difference between married and unmarried people, in addition to the existence of a correlation between the patterns with determination, except for the hierarchical pattern. Based on these results, several recommendations and suggestions were made